2020
DOI: 10.18051/univmed.2020.v39.184-191
|View full text |Cite
|
Sign up to set email alerts
|

Nephrolepis exaltata - Hibiscus rosa-sinensis combination herbal mask decreases levels of reactive oxygen species in nasal wash

Abstract: <strong>Background</strong><br />Poor air and mask quality in the work environment increase the risks of inflammation, reactive oxygen species (ROS) production, ongoing oxidative stress, and superoxide dismutase 3 (SOD3) levels in the airways. The study aimed to investigate the effect of the Nephrolepis exaltata - Hibiscus rosa-sinensis (NE-HRS) combination herbal mask on the airways, as measured by ROS and SOD3 levels in the nasal wash of textile industry workers.<br /><br /><… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…This is consistent with a study of textile factory workers who were exposed to chemicals in the painting process, which found that SOD3 levels decreased when exposed for a longer time (chronic). (19) Furthermore, other studies (20) have shown that short-term exposure to air pollution not only a risk for oxidative damage but also elicits adaptive responses. This condition occurs as an adaptive response by activating a rapid bone marrow response or an early response to cellular signals for gene expression.…”
Section: Analysis Of Trends Differences and Correlation Between Sod3 And Rosmentioning
confidence: 99%
“…This is consistent with a study of textile factory workers who were exposed to chemicals in the painting process, which found that SOD3 levels decreased when exposed for a longer time (chronic). (19) Furthermore, other studies (20) have shown that short-term exposure to air pollution not only a risk for oxidative damage but also elicits adaptive responses. This condition occurs as an adaptive response by activating a rapid bone marrow response or an early response to cellular signals for gene expression.…”
Section: Analysis Of Trends Differences and Correlation Between Sod3 And Rosmentioning
confidence: 99%